2013
DOI: 10.1021/jp402589x
|View full text |Cite
|
Sign up to set email alerts
|

Insight into α-Synuclein Plasticity and Misfolding from Differential Micelle Binding

Abstract: Misfolded species of the 140-residue protein α-synuclein (αS) are implicated in the demise of dopaminergic neurons resulting in fatal neurodegeneration. The intrinsically unstructured protein binds curved synaptic vesicle membranes in helical conformations but misfolds into amyloid fibrils via β-sheet interactions. Breaks in helical αS conformation may offer a pathway to transition from helical to sheet conformation. Here, we explore the evolution of broken αS helix conformations formed in complex with SDS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…We also found that the double-anchor mechanism, which promotes vesicle-vesicle interactions by αS, is enhanced in the presence of cholesterol, thus providing new evidence that the exposure of the region 65-97 in the membrane-bound state of αS is crucial for inducing vesicle clustering (Fusco et al, 2016b). In addition to the possibility that a broken α-helix structure, which is a conformation that αS adopts upon binding with detergent micelles Mazumder et al, 2013), can be involved in the promotion of vesicle-vesicle interactions Snead and Eliezer, 2014), our data indicate that the balance between membrane-bound (ordered) and membrane-detached (disordered) species in the region 65-97 is indeed the crucial modulator of the ability of αS to bridge multiple vesicles and induce their clustering. It is worth noting that our work focuses specifically on the αSmembrane interaction, however, protein-protein interactions at the surface of SV, including binding with VAMP-2 (Burre et al, 2010;Diao et al, 2013) and Rab3a , are also crucial for the regulation of SV trafficking.…”
Section: Discussionmentioning
confidence: 55%
“…We also found that the double-anchor mechanism, which promotes vesicle-vesicle interactions by αS, is enhanced in the presence of cholesterol, thus providing new evidence that the exposure of the region 65-97 in the membrane-bound state of αS is crucial for inducing vesicle clustering (Fusco et al, 2016b). In addition to the possibility that a broken α-helix structure, which is a conformation that αS adopts upon binding with detergent micelles Mazumder et al, 2013), can be involved in the promotion of vesicle-vesicle interactions Snead and Eliezer, 2014), our data indicate that the balance between membrane-bound (ordered) and membrane-detached (disordered) species in the region 65-97 is indeed the crucial modulator of the ability of αS to bridge multiple vesicles and induce their clustering. It is worth noting that our work focuses specifically on the αSmembrane interaction, however, protein-protein interactions at the surface of SV, including binding with VAMP-2 (Burre et al, 2010;Diao et al, 2013) and Rab3a , are also crucial for the regulation of SV trafficking.…”
Section: Discussionmentioning
confidence: 55%
“…A number of groups have proposed that reduced membrane interactions in the central hydrophobic region promote aSyn aggregation at the membrane surface (Bartels et al, 2010; Bodner et al, 2009; Bodner et al, 2010; Dikiy and Eliezer, 2012; Mazumder et al, 2013). To examine this hypothesis, we characterized the aSyn mutants A29E, A30P, V49E, and G51D in terms of their membrane interactions and propensity to undergo membrane-induced aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the hypothesis that exposure of the central hydrophobic region of membrane-bound aSyn favors aSyn aggregation at the membrane surface (Bartels et al, 2010; Bodner et al, 2009; Bodner et al, 2010; Dikiy and Eliezer, 2012; Mazumder et al, 2013), one would predict that A30P, G51D, and A29E, which adopt a relatively exposed conformation in the membrane-bound state, should have a higher propensity to undergo membrane-induced aggregation compared to the WT protein. Conversely, the V49E mutant, which has a lower tendency to adopt an exposed conformation compared to A30P, G51D, and A29E, should have a reduced ability to undergo self-assembly at the membrane surface compared to the other three mutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mazumder et al 11 used molecular dynamics simulations to further characterize the helical conformations of a-synuclein with SDS/SLAS micelles, building upon work of Ferreon et al 12 They identify micelle concentrations and conditions for a-synuclein folding, as well as the transition point from a stable, broken a-helix to a transient b-sheet, which is when pathological amyloid conformations are achievable. The existence of a-synuclein in vivo has proven to be a point of debate, with conflicting data suggesting either an intrinsically disordered monomer or a helically folded tetramer.…”
Section: Studies On Structural Properties Of Idps and Idprsmentioning
confidence: 99%